URINARY HYDROXY-PROLINE ESTIMATION IS CHEAP BIOCHEMICAL MARKER OF BONE TURNOVER IN POST MENOPAUSAL WOMEN - Sabiullah, Mohammed; Suleman, Md Dawood; Rehmatunissa, Rehmatunissa; Ather, Md; Nasreen, Nasreen (Journal of Drug Delivery and Therapeutics, 2015)
Aim: To estimate urinary hydroxy- proline in pre and post menopausalÂ Women as a marker of bone resorption. Materials and methods: This is a prospective, observationalÂ study of 25 healthy post menopausal women with 25 healthy premenopausal women as control conducted at Gandhi Hospital Secunderabad. The study period was between June 2008 to June 2010. 24 hours urinary HydroxyprolineÂ was measured in both cases and controls. Results: The mean urinaryÂ Hydroxyproline in Post menopausal women was 31.64 with standard deviation of 3.37. The mean urinary Hydroxyproline in Pre menopausal women was 19.61 with standard deviation of 2.34. It has got the statistical significance with p value ofÂ <0.0001 Discussion: Fibrillar collagens are rich in the amino acid hydroxyproline, which is excreted in the urine after collagen degradation and are considered to be markers of bone resorption. The urinary excretion of hydroxy proline is increased in states of physiologically high turnover, such as somatic growth, during menopause and high turnover osteopathies.This increased excretion is due to increase in bone loss which was a characteristic feature of the postmenopausal period.Our results show that urinary hydroxy prolineÂ was increased in postmenopausal women compared to premenopausal controls and also urinary hydroxy proline levels were increased more in late postmenopausal women than in early postmenopausal women. Conclusion: In Postmenopausal women with osteoporosis biochemical markers of bone formation decrease and biochemical markers of bone resorptionÂ increases. This is because there is more osteoclastic activity.In our study in post-menopausal womenÂ urinary hydroxy proline level was foundÂ Â to be elevated when compared to pre-menopausal group. Key words: Post menopausal women, Pre menopausal women, Hydroxyproline, Osteoporosis.